Efeitos da acupuntura no tratamento do estresse percebido em gestantes - Costa, Nicolau (2017)
During pregnancy each woman will respond in a particular way to the physical and emotional changes characteristic of this period. Stress is an organic reaction that has physical and / or psychological components, which can affect pregnant women, requiring treatment. The study aimed to analyze the effects of acupuncture in the treatment of perceived stress in pregnant women. Almost experimental study, before and after the Family Development Center / UFC, with 56 pregnant women at normal risk. Six sessions of acupuncture were performed with each pregnant woman, and the frequency of two sessions per week. Before the beginning of the therapy, a sociodemographic, clinical and obstetrical data collection instrument was used and the stress perceived by the pregnant woman through the Global Perceived Stress Scale (PSS10) was evaluated. The scale was applied weekly to verify the evolution of the stress scores of the pregnant women during the treatment. The R Core Team R Software was used for statistical analysis. The ethical and legal aspects surrounding human research were respected. The majority of the pregnant women were between the ages of 20 and 29, with high school, living in the capital, with income of up to two minimum wages, housewives, living with a partner. They were in the first gestation, in the third trimester of pregnancy and did not perform physical activities. In the initial session, the overall mean score of the stress scale was 22.41. After the beginning of acupuncture, the mean points decreased to 19.15, reaching up to 16.65 points, representing a decrease of 5.76 points during the treatment. A significant difference between the initial measurement and all other treatment sessions was observed. It was concluded that the use of acupuncture for the treatment of stress during pregnancy was effective, reducing all the negative characteristics of the stress perceived by the pregnant women.